Correlation Work Period And Hand Position When Driving With Shoulder Pain On Bus Driver At Boyolali District - Pambudi, Bagus; , Yulisna Mutia Sari, SSt.FT., M.Sc (); , Maskun Pudjianto, SMPh., S.Pd., M.Kes (2016)
Background: One of the factors of shoulder pain experienced bus driver is working attitude that is not natural that causes the body to move away from the natural position, for example shoulder or arm too up.. Another factor is the long working lives or period of work with activities that focus on human power can cause more severe diseases, especially of the musculoskeletal system. Purpose: To determine the relationship between working lives and hand position when driving with complaints of shoulder pain on bus driver. Aims of Research: To inform and evaluation for bus driver that work is being undertaken potentially lead to musculoskeletal disorders, one of which is in the form shoulder pain so that workers can anticipate and take steps to prevent as well as improvements in the workplace. Research Method: This research was using observational research with cross sectional approach. The sampling technique used purposive sampling, as many as 74 respondents. Measuring tool research using interviews with the questionnaire sheet, RULA (Rapid Upper Limb Assessment) and VDS (Verbal Descriptive Scale). The statistical test used was chi-square. Result: From statistic analysis that risk level of hand position with shoulder pain showed p-value 0.113 or probability (significance) > 0.05, For the period of work with shoulder pain showed p-value 0.000 or probability (significance) < 0.05 . Conclusion: There is relationship between working period with shoulder pain and there is no relationship between hend position when driving on bus drver at Boyolali District.